RELATED FACTORS OF CARPAL TUNNEL SYNDROME (CTS) AMONG ONION SKIN PEELER WORKER AT SEGIRI SAMARINDA, EAST KALIMANTAN - Setyowati, Dina Lusiana; Dwijayanti, Dyah; Sultan, Muhamad (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2015)
Various activities that involve hands repetitively are often associated with Carpal Tunnel Syndrome (CTS). CTS is defined by compression of the median nerve in the wrist. Peeling onion skin is a risk job which can be easily affected by CTS. The purpose of this study was to determine the relationship between repetitive motions, duration of work, work of service, the history of Illness and CTS among onion skin peeler workers at Segiri Market Samarinda. This research used a cross-sectional design to analyze the relationship among the variables. The subject of this study were people who work as peel onion in the Segiri Market Samarinda and the sampling method of this research using purposive sampling with 31 participants. Data was analysed using Chi-Square by SPSS 16 Program with significance level of 0.05 (5%). The results showed that there was a correlation between repetitive motions(p = 0.008),duration of work (p = 0.000), work of service (p = 0.034) and CTS; and there was no relationship between history of Illness and CTS (p = 1.000). The conclusion of the research that there was a relationship between repetitive motions, duration of work, work of service and Carpal Tunnel Syndrome (CTS); and there was no relationship between history of Illness and Carpal Tunnel Syndrome (CTS). Keywords : CTS, Duration of Work, Work of service, History of Disease, Repetitive Movement